The Effect of Liquidity, Activity, Profitability, and Leverage on The Financial Distress of Properties And Real Estate Companies in 2019-2022 - Jessie, Jessie; Tannia, Tannia (Dinasti International Journal of Management Science, 2024)
The purpose of this study is to examine how financial distress is affected by liquidity, activity, profitability, and leverage in real estate and property companies that are listed on the Indonesia Stock Exchange between 2019 and 2022. This study is inspired by the recent financial distress of major industry participants such as FORZ, COWL, MYRX, and ARMY. The approach in this study is quantitative, and the data was gathered using a documentation technique with a sample of 33 companies. This study is conducted with panel data regression using Eviews 12. The results of this study reveal that liquidity, activity, profitability, and leverage simultaneously have a significant impact on financial distress. Liquidity and profitability partially exhibit negative and significant effects on financial distress, while leverage has a positive and significant impact on financial distress. However, activity alone does not significantly affect financial distress. In addition, the findings affirm that the risk of financial distress can be influenced by financial factors such as liquidity, activity, profitability, and leverage.